2015
DOI: 10.1103/physrevd.92.084055
|View full text |Cite
|
Sign up to set email alerts
|

Charged Einstein-aether black holes and Smarr formula

Abstract: In the framework of the Einstein-Maxwell-aether theory, we present two new classes of exact charged black hole solutions, which are asymptotically flat and possess the universal as well as Killing horizons. We also construct the Smarr formulas, and calculate the temperatures of the horizons, using the Smarr mass-area relation. We find that, in contrast to the neutral case, such obtained temperature is not proportional to its surface gravity at any of the two kinds of the horizons. Einstein-Maxwell-aether black… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 58 publications
5
85
0
Order By: Relevance
“…The boundary conditions on the metric components are such that the solution is asymptotically flat, while those for the aether components are such that lim r→+∞ u a = (1, 0, 0, 0). (2.18) As shown in [49], there exist two types of exact static and charged spherically symmetric black hole solutions in Einstein-aether theory. The first solution corresponds to the special choice of coupling constants c 14 = 0 and c 123 = 0 where c 123 ≡ c 1 + c 2 + c 3 , while the second solution corresponds to c 123 = 0.…”
Section: B Static and Charged Spherically Symmetric Einstein-aether mentioning
confidence: 99%
“…The boundary conditions on the metric components are such that the solution is asymptotically flat, while those for the aether components are such that lim r→+∞ u a = (1, 0, 0, 0). (2.18) As shown in [49], there exist two types of exact static and charged spherically symmetric black hole solutions in Einstein-aether theory. The first solution corresponds to the special choice of coupling constants c 14 = 0 and c 123 = 0 where c 123 ≡ c 1 + c 2 + c 3 , while the second solution corresponds to c 123 = 0.…”
Section: B Static and Charged Spherically Symmetric Einstein-aether mentioning
confidence: 99%
“…However, this seems true only for neutral case. When the black hole is charged, such a law is still absent [28]. In addition, using the Hamilton-Jacobi method, quantum tunneling of non-relativistic particles with a general non-linear dispersion relation was studied [29], and it was found that different species of particles in general experience different temperatures, 9) where κ U H is the surface gravity calculated from Eq.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we can calculate the surface gravity at the universal horizon of a charged Einstein-aether black hole [39]. The static spherically symmetric spacetime in Einstein-Maxwell-aether theory takes the Eddington-Finklestein coordinates form (2.3).…”
Section: Surface Gravity Of a Charged Einstein-aether Black Holementioning
confidence: 99%